Цивільно-правове регулювання захисту прав дітей в Україні - Кириченко, Т. С.; Kyrychenko, T. S.; ORCID: https://orcid.org/0000-0002-8785-0475 (Юридичний науковий електронний журнал. - 2023. - № 2. - С. 155-158, 2023)
Проаналізовано національне та міжнародне законодавства щодо правового регулювання відносин щодо захисту прав дітей в Україні. Зазначено, що в Україні основні підходи до осмислення й реалізації прав дітей, визначених міжнародним та вітчизняним законодавством, протягом останнього часу істотно змінилися. Це пов’язано з посиленням уваги з боку держави до інтересів дітей, удосконаленням механізму контролю за дотриманням чинного законодавства у сфері охорони дитинства, розвитком інституцій соціально-правового захисту дітей та багатьма іншими факторами.

The article is devoted to the analysis of national and international legislation regarding the legal regulation of relations regarding the protection of children’s rights in Ukraine. In Ukraine, a clear mechanism for ensuring the implementation and monitoring the implementation of the norms of family legislation related to the education and protection of children’s rights has not yet been developed. Among the normative acts regulating children’s rights in Ukraine, there are many laws. Ukraine has also ratified many international acts and treaties on the protection of children’s rights, but the problems do not decrease. Every year, about 8 thousand children are left without parental care, many children are in very terrible living conditions due to difficult life circumstances, irresponsible attitude of parents to fulfill their duties, parents’ use of alcohol and drugs, as well as due to their cruel treatment of the child. In Ukraine, the term «social orphans» is being used more and more often - such a socio-demographic group of children who, as a result of social, economic, and other reasons, remained orphans, and their parents were deprived of parental rights. The main characteristics of modern life are deep integration processes that concern various spheres of life. Currently, migration processes are intensifying and many legal relations arise outside the borders of one state and need to be settled outside the borders of another state. The main desire for all Ukrainians is to become a democratic state in which laws work, where people have certain freedom and equal rights. You can talk as much as you want about democracy, freedom, and equality, but the level of freedom and democracy in society is determined by the power of human rights and freedoms, including the official ratification of international legal acts that regulate them. A special category of children is children who are the least protected, they depend on the will and decisions of adults, often cannot independently protect their rights, do not have the knowledge of where to turn for necessary help, and do not have the knowledge and skills to protect themselves. Also, in the conditions of the modern crisis and war, socio-economic problems in society are worsening, all this affects the increase in cases of children falling into difficult life circumstances, committing child abuse, domestic violence, involvement of children in criminal groups, involvement in begging, to the worst forms of child labor, etc.

Проанализировано национальное и международное законодательство о правовом регулировании отношений по защите прав детей в Украине. Отмечено, что в Украине основные подходы к осмыслению и реализации прав детей, определенных международным и отечественным законодательством, за последнее время существенно изменились. Это связано с усилением внимания со стороны государства к интересам детей, усовершенствованием механизма контроля за соблюдением действующего законодательства в сфере охраны детства, развитием институтов социально-правовой защиты детей и многими другими факторами.
Civil-legal regulation of the protection of children’s rights in Ukraine
Кириченко, Т. С. Цивільно-правове регулювання захисту прав дітей в Україні [Електронний ресурс] / Кириченко Т. С. // Юридичний науковий електронний журнал. - 2023. - № 2. - С. 155-158. – Режим доступу: http://www.lsej.org.ua/2_2023/34.pdf.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Міжнародне право .International Law. Международное право; діти; children; дети; правове регулювання; legal regulation; правовое регулирование; Сімейне право. Family law. Семейное право; законодавство; legislation; законодательство; міжнародні правові акти; international legal acts; международные правовые акты; захист прав дітей; protection of children's rights; защита прав детей